Factors Contributing towards Stigmatisation of Offenders in Singapore. Issue 6 (1st November 2016) - Tan, Xiao Xian; Chu, Chi Meng; Tan, Gabriel
Abstract : Stigmatisation is a frequently listed as a concern by offenders and has been identified as a major barrier to reintegration. The present study explored factors contributing to stigmatising attitudes towards various sub-types of offenders in Singapore. Six hundred and twenty-eight undergraduate students read a vignette illustrating a sexual, a white-collar, or a violent crime before answering various questionnaires in an online survey. Previous contact with offenders was not related to desire for social distance from them. However, respondents who perceived offenders as incapable of changing, as well as those who felt more morally outraged by the crimes they had committed, indicated a greater desire for social distance from offenders. Respondents also had a tendency to desire distance from sexual and violent offenders more than they did from white-collar offenders. The findings extend the understanding of pathways leading towards stigmatisation of offenders and have implications for policy-making and reintegration efforts.